2013
DOI: 10.1186/1471-227x-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of alcohol misuse, HIV sexual risk and HIV screening uptake among emergency department patients

Abstract: BackgroundEmergency department (ED) patients comprise a high-risk population for alcohol misuse and sexual risk for HIV. In order to design future interventions to increase HIV screening uptake, we examined the interrelationship among alcohol misuse, sexual risk for HIV and HIV screening uptake among these patients.MethodsA random sample of 18-64-year-old English- or Spanish-speaking patients at two EDs during July-August 2009 completed a self-administered questionnaire about their alcohol use using the Alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…This finding is coherent with studies showing that alcohol-dependent individuals have a higher prevalence of HCV than those who are not (Siu et al, 2009). This could be related to the high incidence of sexual risk behavior in alcohol users (Trillo et al, 2013) and the immunosuppressive effect of alcohol (Carrière et al, 2006;Geissler et al, 1997). Moreover, the older mean age of ALC patients is a characteristic associated with higher risk of hepatitis (Stein et al, 2012), probably because an older age may involve a longer exposure period to drug-related risks, including risk behaviors such as those associated to HCV and HBV infection.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is coherent with studies showing that alcohol-dependent individuals have a higher prevalence of HCV than those who are not (Siu et al, 2009). This could be related to the high incidence of sexual risk behavior in alcohol users (Trillo et al, 2013) and the immunosuppressive effect of alcohol (Carrière et al, 2006;Geissler et al, 1997). Moreover, the older mean age of ALC patients is a characteristic associated with higher risk of hepatitis (Stein et al, 2012), probably because an older age may involve a longer exposure period to drug-related risks, including risk behaviors such as those associated to HCV and HBV infection.…”
Section: Discussionmentioning
confidence: 97%
“…Based on our previous studies, 61,62 we calculated an HIV/HCV sexual risk behavior score using the relevant items from the HIV/HCV risk behavior questionnaire. The score was the sum of the risk behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Independent studies have identified ED patients as being at relatively high risk of both heavy alcohol use (Cohen et al, 2007) and HIV infection (Alpert et al, 1996; Trillo et al, 2013). With approximately 56,000 new HIV cases per year (CDC, 2012), it is important to identify the associations between alcohol use and increased risks of HIV infection.…”
Section: Summary and Objectivementioning
confidence: 99%
“…Further, individuals consuming alcohol prior to or at the time of sex were at a 87% increased risk, and individuals engaging in binge drinking (5 or more drinks in 1 sitting for men, 4 for women) had twice the risk of nonbinge drinkers for HIV-incident infection (Baliunas et al, 2010). Specific to ED populations, 1 investigation found evidence of a significant positive relationship between reported sexual risk of HIV and alcohol use among men and women patients, with women who reported binge drinking more likely to have higher reported sexual risk of HIV compared to women who did not report binge drinking (Trillo et al, 2013). In addition, Fenton (2007) reports that more new HIV cases are diagnosed among ED patients compared to patients in any other clinic setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation